2011 IEEE 17th International Symposium on High Performance Computer Architecture 2011
DOI: 10.1109/hpca.2011.5749722
|View full text |Cite
|
Sign up to set email alerts
|

Addressing system-level trimming issues in on-chip nanophotonic networks

Abstract: The basic building block of on-chip nanophotonic interconnects is the microring resonator [14], and these resonators change their resonant wavelengths due to variations in temperature -a problem that can be addressed using a technique called "trimming", which involves correcting the drift via heating and/or current injection. Thus far system researchers have modeled trimming as a per ring fixed cost. In this work we show that at the system level using a fixed cost model is inappropriate -our simulations demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 24 publications
(39 reference statements)
2
46
0
Order By: Relevance
“…However, the average trimming power per microring is actually 18% higher for CrON. In [12] we observed that the heating power required for trimming has a non-linear relationship with microring count, and our findings show that current injection has a nonlinear relationship as well. CrON requires more trimming power per microring since the network operates at a higher temperature due to the greater power consumption when compared to DCAF.…”
Section: Power Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…However, the average trimming power per microring is actually 18% higher for CrON. In [12] we observed that the heating power required for trimming has a non-linear relationship with microring count, and our findings show that current injection has a nonlinear relationship as well. CrON requires more trimming power per microring since the network operates at a higher temperature due to the greater power consumption when compared to DCAF.…”
Section: Power Resultsmentioning
confidence: 60%
“…We used the Mintaka simulator to conduct these experiments. We will briefly describe the simulator here -for more details please see [12] and [14].…”
Section: Mintakamentioning
confidence: 99%
See 2 more Smart Citations
“…Ye et al [10] presented a system-level analytical thermal model for general ONoCs and analyzed the thermal power of the optical devices. Nitta et al [11] analyzed the trimming power of the microrings when the temperature changes firstly and then proposed the SRW and PMMA-clad resonators to decrease the trimming power. Xu et al [12] proposed a series of solutions to the wavelength drifting problem of microrings and bandwidth loss problem of the optical network, due to PV.…”
Section: Related Workmentioning
confidence: 99%